(untitled) (Scientific journal of the Fergana State University, 2023)
Islamic jurisprudence is one of the earliest and most developed branch of oriental studies. The extensive study of Islamic law by Western scholars began during the European colonial expansion and the modern discipline of "Islamic law" took shape in the middle of the 19th century. During this period, orientalists-historians produced their main works, which formed the first scientific understanding of Muslim law in the West. This article provides a brief description of Josef Schacht, one of the scholars who conducted research on Islamic law and whose research is currently guiding European orientalists in this area.